Zooplankton measurements in the Coquimbo upwelling system during the year 2023 - Victor M Aguilera; Linda Barranco; Pablo Gorostiaga (PANGAEA, 2025)
A series of discrete measurements were obtained on a near-monthly basis in a subtropical upwelling area of the Humboldt Current System during the year 2023. These included temperature, salinity, dissolved oxygen, fluorescence, and pH profiles, as well as measurements of zooplankton biomass and chlorophyll- and particulate organic carbon (POC) concentrations. The estimation of zooplankton biomass was derived from dry weight, assuming a carbon content of 40%. The measurements were conducted under distinct warm events associated with the ENSO dynamic. The objective of this study was to evaluate the influence of remote (ENSO) and upwelling forcing on the intraseasonal variability of zooplankton biomass.